Sistema de gestión de la información para los procesos de evaluación de la carrera de Ingeniería Electromecánica: Módulos Pertinencia, Plan Curricular y Academia - Villazhagñay Pallo, Carolina Elizabeth (2018)
For the present technological proposal a Web System has been designed that allows to manage the evaluation process of the Electromechanical Engineering career. The system has been developed on the basis of the Career Assessment Model of the Council for the Evaluation, Accreditation and Quality Assurance of Higher Education (CEAACES) and is it composed of the modules of Relevance, Curricular and Academic Plan, in which it will develop the following processes: Start Session, Manage Coordinator, Manage Teaching, Assign Qualifications, View Reports, Upload Files and Manage Modules. For the development we used Visual Studio.Net, a Microsoft tool that integrates the programming language "C #", which allows the development of web applications in a fast and efficient way through a three-layer architecture called "Model - View - Controller ", by means of which the information, the logic of the system and the interface presented to the user are classified. Likewise, "SQL Server 2012" was used to manage the database, since it allows not only the integration with the programming language used, but also offers good security guarantees in the storage of information. Regarding the development methodology, the Iterative - Incremental model was used, which allowed to organize the project in iterations, which represent the needs to be solved, giving the possibility of making small deliveries completely functional to the user and thus be able to reach a complete version of the system that becomes the final product of the project. As a result of this proposal we have a software in operation and approved by the user, which allows us to conclude that all the objectives set out at the beginning of the work have been met, delivering a technological tool that helps improve the management of the processes of self-evaluation of the career and that allows above all to obtain automatic reports with the results of the evaluations, the same ones that must serve for the taking of anticipated decisions to the real evaluations that will be executed by the CEAACES.